The Influence Of Reward And Punishment On Employee Performance At CV. Dinamika Mitra Nusantara, Bengkulu City - Anugerah , Yeza Dwi; Susena, Karona Cahya; Febliansa, M Rahman (Universitas Dehasen Bengkulu, 2025)
Dinamika Mitra Nusantara of Bengkulu City, which was established in 2018 and is engaged in the distribution sector such as Tires, Oil, and Car Spare Parts and Heavy Equipment for Mining and Coal Companies, is one of the companies that faces challenges in maintaining productivity and optimal employee contribution to achieving targets. In recent years, employee performance has not been optimal, marked by decreased productivity, late assignments, and minimal innovation. The type of research conducted in this study is causal associative research with quantitative techniques. The sample of this study was 37 people who were staff and employees at CV. Dinamika Mitra Nusantara of Bengkulu City. Data collection using questionnaires and the analysis methods used were multiple linear regression, determination test and hypothesis test. The results of the regression analysis show that Reward (X1) has a significance value of 0.019 (<0.05), so Ho is rejected and Ha is accepted. This means that rewards have a significant effect on employees’ performance. The punishment variable (X2) has a significance of 0.000 <0.05, so Ho is rejected and Ha is accepted. This means that punishment has a significant effect on employees’ performance. And the simultaneous application of reward and punishment has a positive and significant impact on improving employees’ performance at CV. Dinamika Mitra Nusantara of Bengkulu City. This is evidenced by a significance value of 0.00 (<0.05) and F count of 87.853 with a significance of 0.000. Employees become more motivated because they feel that rewards and sanctions are given in a balanced manner. Thus, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected.